2012
DOI: 10.1111/j.1365-2966.2012.21465.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition of ultracompact dwarf galaxies in the Virgo and Fornax clusters

Abstract: We present spectroscopic observations of ultracompact dwarf (UCD) galaxies in the Fornax and Virgo clusters made to measure and compare their stellar populations. The spectra were obtained on the Gemini‐North (Virgo) and Gemini‐South (Fornax) telescopes using the respective Gemini Multi‐Object Spectrographs. We estimated the ages, metallicities and abundances of the objects from measurements of Lick line‐strength indices in the spectra; we also estimated the ages and metallicities independently using a direct … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 61 publications
5
61
1
Order By: Relevance
“…The properties of UCDs are similar to those of nuclear clusters: as well as those listed above, the metallicities (Brodie et al 2011;Francis et al 2012), internal velocity dispersions ) and colour-magnitude re- (Cote et al 2006;Evstigneeva et al 2008;Brüns et al 2011) are similar to those of dwarf galaxy nuclei. Simulations of the threshing scenario performed by Bekki et al (2001Bekki et al ( , 2003 produce objects with sizes and luminosities comparable with observed UCDs.…”
Section: Introductionsupporting
confidence: 63%
“…The properties of UCDs are similar to those of nuclear clusters: as well as those listed above, the metallicities (Brodie et al 2011;Francis et al 2012), internal velocity dispersions ) and colour-magnitude re- (Cote et al 2006;Evstigneeva et al 2008;Brüns et al 2011) are similar to those of dwarf galaxy nuclei. Simulations of the threshing scenario performed by Bekki et al (2001Bekki et al ( , 2003 produce objects with sizes and luminosities comparable with observed UCDs.…”
Section: Introductionsupporting
confidence: 63%
“…In both objects, we assumed solar metallicities. However, if the metallicity were significantly below solar, this could lead to an overestimate of the population mass estimates; this seems possible in VUCD3,where the existing measurements span a wide range from [Z/H]=−0.28 to 0.35 (Evstigneeva et al 2007;Firth et al 2009;Francis et al 2012). GC dynamical mass estimates also seem to be lower than expected Kimmig et al 2015), though this appears to be in part because of mass segregation within the clusters combined with the assumption of mass-traces-light models (Shanahan & Gieles 2015;Baumgardt 2017).…”
Section: Isotropic Model Resultsmentioning
confidence: 99%
“…VUCD3 is located 14kpc in projection from the center of M87 and has M 12.75 V = - (Mieske et al 2013). The metallicity of VUCD3 has been estimated to be between −0.28 and 0.35 in several studies (Evstigneeva et al 2007;Firth et al 2009;Francis et al 2012), and it has an [α/Fe]∼0.5 (Francis et al 2012). M59cO is located 10kpc in projection from the center of M59 and has M 13.26 V = - (Mieske et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This makes them analogous to ultra-compact dwarf (UCDs) galaxies (Drinkwater et al 2003) observed in the nearby Virgo and Fornax clusters, which are known to have mass-tolight ratios consistent with the Kroupa IMF when the two-body relaxation timescales are long (Chilingarian et al 2011). UCDs are proven to be tidally stripped galactic nuclei by the recent discovery of central massive black holes (Seth et al 2014) and by their stellar population properties (Francis et al 2012) similar to much more massive tidally stripped M32-like compact elliptical galaxies (Chilingarian et al 2009;Chilingarian & Zolotukhin 2015). The only known stellar systems where central luminosity densities exceed 10 5 L pc −3 are nuclear star clusters in low and intermediate luminosity galaxies, cEs, some UCDs (Evstigneeva et al 2008) and some globular clusters.…”
Section: Discussionmentioning
confidence: 99%